TI_GERICHTE 52.2016.107 vom 16. Januar 2017 , Credito per la realizzazione di opere di urbanizzazione - Contestazioni pianificatorie - TI Tribunale d'appello (2017)
Credito per la realizzazione di opere di urbanizzazione - Contestazioni pianificatorie